LABORATÓRIO DE ENSINO DE MATEMÁTICA - APOIO À EDUCAÇÃO BÁSICA E A FORMAÇÃO DE PROFESSORES - Olegario, Anisia; Nehring, Cátia M.; Pozzobon, Marta C. C.; Duarte, Kelly P. (Salão do Conhecimento, 2013)
Resumo